A Comparative Study about Vertical Accuracy of Four Freely Available Digital Elevation Models - Ferreira, Zuleide Alves (2022)
Ferreira, Z. A., & Cabral, P. (2022). A Comparative Study about Vertical Accuracy of Four Freely Available Digital Elevation Models: A Case Study in the Balsas River Watershed, Brazil. ISPRS International Journal of Geo-Information, 11(2), 1-14. [106]. https://doi.org/10.3390/ijgi11020106 -----------------------------------------------Funding: This study was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia) under the project UIDB/04152/2020 (Centro de Investigação em Gestão de Informação (MagIC) and the Instituto Federal de Educação, Ciência e Tecnologia do Tocantins (Campus Palmas)).